2017
DOI: 10.2147/ijn.s128030
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-incorporated collagen hydrogels improve cell alignment and the performance of cardiac constructs

Abstract: Carbon nanotubes (CNTs) provide an essential 2-D microenvironment for cardiomyocyte growth and function. However, it remains to be elucidated whether CNT nanostructures can promote cell–cell integrity and facilitate the formation of functional tissues in 3-D hydrogels. Here, single-walled CNTs were incorporated into collagen hydrogels to fabricate (CNT/Col) hydrogels, which improved mechanical and electrical properties. The incorporation of CNTs (up to 1 wt%) exhibited no toxicity to cardiomyocytes and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…CNTs have been proposed to act as electrical shortcuts and confirmed beneficial to cellular growth . They were employed by Sun et al to improve mechanical elasticity, as well as impart electrical conductivity to a collagen hydrogel . 1 wt% CNT–collagen hydrogel proved best for neonatal rat ventricular myocytes growth, while 2 wt% leads to toxicity.…”
Section: Conductive Scaffolds For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…CNTs have been proposed to act as electrical shortcuts and confirmed beneficial to cellular growth . They were employed by Sun et al to improve mechanical elasticity, as well as impart electrical conductivity to a collagen hydrogel . 1 wt% CNT–collagen hydrogel proved best for neonatal rat ventricular myocytes growth, while 2 wt% leads to toxicity.…”
Section: Conductive Scaffolds For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…The framework of such materials is a branched CNT network, and the filler is one of the proteins or a protein complex. The effectiveness of the use of CNT for cardiac regeneration is confirmed by the results of many papers [13][14][15][16]. It has been established that the introduction of CNTs into the structure of polymer 124 increases electrical conductivity and improves the excitation threshold of a biomass material [13].…”
Section: Introductionmentioning
confidence: 80%
“…A hydrogel based on methacrylate anhydride and CNT was developed in [14] to support the functioning and growth of cardiomyocytes. It has been shown that the collagen hydrogel reinforced with CNTs significantly improves the functioning of cardiomyocytes [15]. It was found that the addition of CNT improves the structural integrity and biomechanical properties of film bioconstructions from chitosan, and as a result promotes proliferation and differentiation of myofibroblasts without induction of toxicity and apoptosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotube-injectable hydrogel can increase cell adhesion sites and ameliorate the arrangement structure of hydrogels to ensure cell-to-cell integrity to increase the survival rate of cardiomyocytes. For instance, carbon nanotube-incorporated collagen hydrogels can improve arrangement to promote cellcell integrity and accelerate the regeneration of functional tissues in 3-D hydrogels (Sun et al, 2017). Recently, in addition to superior biocompatibility and electrical conductivity as well as appropriate adhesion sites, the nanotube composite injectable hydrogels were designed to provide sites for bioactive substance adhesion.…”
Section: Nanoparticles and Nanotubesmentioning
confidence: 99%